Concentration-dependent alpha1-Adrenoceptor Antagonism and Inhibition of Neurogenic Smooth Muscle Contraction by Mirabegron in the Human Prostate - Huang, Ru; Liu, Yuhan; Ciotkowska, Anna; Tamalunas, Alexander; Waidelich, Raphaela; Strittmatter, Frank; Stief, Christian G.; Hennenberg, Martin (Frontiers in Pharmacology, 2021)
Introduction: Mirabegron is available for treatment of storage symptoms in overactive bladder, which may be improved by β3-adrenoceptor-induced bladder smooth muscle relaxation. In addition to storage symptoms, lower urinary tract symptoms in men include obstructive symptoms attributed to benign prostatic hyperplasia, caused by increased prostate smooth muscle tone and prostate enlargement. In contrast to the bladder and storage symptoms, effects of mirabegron on prostate smooth muscle contraction and obstructive symptoms are poorly understood. Evidence from non-human smooth muscle suggested antagonism of α1-adrenoceptors as an important off-target effect of mirabegron. As α1-adrenergic contraction is crucial in pathophysiology and medical treatment of obstructive symptoms, we here examined effects of mirabegron on contractions of human prostate tissues and on proliferation of prostate stromal cells. Methods: Contractions were induced in an organ bath. Effects of mirabegron on proliferation, viability, and cAMP levels in cultured stromal cells were examined by EdU assays, CCK-8 assays and ELISA. Results: Mirabegron in concentrations of 5 µM and 10 µM, but not 1 µM inhibited electric field stimulation-induced contractions of human prostate tissues. Mirabegron in concentrations of 5 µM and 10 µM shifted concentration response curves for noradrenaline-, methoxamine- and phenylephrine-induced contractions to the right, including recovery of contractions at high concentrations of α1-adrenergic agonists, increased EC50 values, but unchanged Emax values. Rightshifts of noradrenaline concentration response curves and inhibition of EFS-induced contractions were resistant to L-748,337, L-NAME, and BPIPP. 1 µM mirabegron was without effect on α1-adrenergic contractions. Endothelin-1- and U46619-induced contractions were not affected or only inhibited to neglectable extent. Effects of mirabegron (0.5-10 µM) on proliferation and viability of stromal cells were neglectable or small, reaching maximum decreases of 8% in proliferation assays and 17% in viability assays. Mirabegron did not induce detectable increases of cAMP levels in cultured stromal cells. Conclusions: Mirabegron inhibits neurogenic and α1-adrenergic human prostate smooth muscle contractions. This inhibition may be based on antagonism of α1-adrenoceptors by mirabegron, and does not include activation of β3-adrenoceptors and requires concentrations ranging 50-100fold higher than plasma concentrations reported from normal dosing. Non-adrenergic contractions and proliferation of prostate stromal cells are not inhibited by mirabegron.